Bluetongue, Schmallenberg - what is next? Culicoides-borne viral diseases in the 21(st) Century - Koenraadt, Constantianus JM (BioMed Central, 2014)
In the past decade, two pathogens transmitted by Culicoides biting midges (Diptera: Ceratopogonidae), bluetongue virus and Schmallenberg virus, have caused serious economic losses to the European livestock industry, most notably affecting sheep and cattle. These outbreaks of arboviral disease have highlighted large knowledge gaps on the biology and ecology of indigenous Culicoides species. With these research gaps in mind, and as a means of assessing what potential disease outbreaks to expect in the future, an international workshop was held in May 2013 at Wageningen University, The Netherlands. It brought together research groups from Belgium, France, Germany, Spain, Switzerland, United Kingdom and The Netherlands, with diverse backgrounds in vector ecology, epidemiology, entomology, virology, animal health, modelling, and genetics. Here, we report on the key findings of this workshop.